Pem Pemberdayaan Kelompok Tani Kulo Melalui Diversifikasi Pengolahan Kacang Tanah Lokal Desa Teluk Menjadi Susu Dan Selai Kacang Tanah (Arachis hypogaea) - Novita, Sri (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
Groundnut is one of the commodities from Teluk Village, Pemayung Sub-district. The peanut variety in Teluk Village is the large type of garuda with 3-4 seeds, so it has great potential to be developed and marketed outside the village. However, the sale of peanuts is only in its raw form, without further processing. Through the PPK Ormawa Tymac activity, higher education institutions play a role in transferring knowledge, in terms of diversifying peanut-based products. The products processed in this activity include peanut milk and peanut butter. The PPK Ormawa Tymac team also facilitates the making of NIB, registration of IPR, helps find partners and creates an e-commerce platform (shopee) to market products. To be able to achieve the objectives, the implementation method is used with the Participatory Rural Appraisal (PRA) approach, which is an approach that prioritizes the results of the formulation according to the needs in organizing PPK Ormawa Tymac activities.